DEVELOPMENT OF A DATA PROCESSING PROGRAM FOR TRACK IRREGULARITIES MEASURED BY TRACK RECORDING CARS AS INPUT DATA ON TRACK IRREGULARITIES IN THE UNIVERSAL MECHANISM SOFTWARE - Daniel Sianipar, Hotashi
Track irregularity data is required in railway design as input for dynamic simulations. Measurement data of track irregularities obtained from track recording vehicles needs to be processed before use. A program to process this data has been developed by PPTI KA FTMD ITB and needs to be validated and refined before industry implementation. The research begins with the modeling and validation of the track recording vehicle. The processed track irregularity data using the program and the resulting acceleration response from the simulation are compared with other irregularity data for program evaluation. The evaluation revealed issues with the program. Based on this evaluation, modifications were made to the program. These modifications were successful, as evidenced by the simulation acceleration after the modifications. Subsequently, the simulation acceleration was compared with the measured acceleration. The analysis of acceleration after modification shows that the vertical acceleration on the left axle in the simulation resembles the measured acceleration. The vertical acceleration of the carbody in the simulation also resembles the measured acceleration, but the lateral acceleration of the carbody differs. These differences may be due to the quality of the measurements, data processing, and the modeling of the measuring train.